An efficient algorithm to compute the exponential of skew-Hermitian matrices for the time integration of the Schrödinger equation - Bader, P.; Blanes, S.; Casas, F.; Seydaoğlu, M. (Elsevier B.V., 2022)
We present a practical algorithm to approximate the exponential of skew-Hermitian matrices up to round-off error based on an efficient computation of Chebyshev polynomials of matrices and the corresponding error analysis. It is based on Chebyshev polynomials of degrees 2, 4, 8, 12 and 18 which are computed with only 1, 2, 3, 4 and 5 matrix–matrix products, respectively. For problems of the form exp(?iA), with A a real and symmetric matrix, an improved version is presented that computes the sine and cosine of A with a reduced computational cost. The theoretical analysis, supported by numerical experiments, indicates that the new methods are more efficient than schemes based on rational Padé approximants and Taylor polynomials for all tolerances and time interval lengths. The new procedure is particularly recommended to be used in conjunction with exponential integrators for the numerical time integration of the Schrödinger equation. © 2021 International Association for Mathematics and Computers in Simulation (IMACS)
Keywords: Matrix cosine; Matrix exponential; Matrix polynomials; Matrix sine; Schrödinger equation; Computational efficiency; Integral equations; Numerical methods; Polynomials; Chebyshev polynomials; matrix; Matrix cosine; Matrix exponentials; Matrix polynomials; Matrix sine; Schrödinge equation; Skew-Hermitian matrix; Matrix algebra